Transcranial magnetic stimulation for treatment of major depression during pregnancy: a review - Felipe,Renata de Melo (2016)
Abstract Introduction: Pregnancy is characterized by a high prevalence of mental disorders. Depression is the most common of these disorders and it is a risk factor for negative maternal and child development outcomes. Psychotherapy and pharmacotherapy are conventional and well-established therapeutic options, but some clients fail to respond and the safety of using some pharmacological agents during pregnancy is unclear. Some neuromodulation techniques, such as repetitive transcranial magnetic stimulation (rTMS), have been studied in depressed pregnant women. Objective: To evaluate the safety and efficacy of rTMS for major depression in pregnant women. Methods: The LILACS and PubMed databases were reviewed using the search terms depression, pregnancy and magnetic stimulation. Texts including primary data, published in Portuguese, Spanish, or English, between 1995 and 2014, that evaluated depressed pregnant women and used rTMS as the intervention were selected. Papers lacking sufficient data were excluded. Twenty-two texts were initially identified; after applying the inclusion criteria, 12 were selected and analyzed. Results: The studies reviewed reported satisfactory responses to rTMS in acute depressive episodes, as measured using depressive symptom scales. Remission of symptoms was achieved in many cases. The procedure was well tolerated and there were no reports of damage/complications to unborn children. Conclusion: The data available at this time support the efficacy and tolerability of rTMS for depression in pregnant women. Controlled studies should corroborate this conclusion. This review only included studies in three languages and the resulting sample size was not large enough to conduct a meta-analysis.